Mixed convection in a lid-driven enclosure filled with hybrid nanofluid by finite volume method - Ridha Ali, Inas (2022)
The heat transfer process in complex geometries is essential due to its wide range of industrial and engineering applications. Understanding fluid flow patterns and convection heat transfer will give scientists or engineers the idea to manipulate the process to achieve the desired results. For the past decade, researchers reported that nanofluid enhances heat transfer and fluid flow. With rapid development in engineering, scientists and engineers have begun to study the fluid flow and heat transfer pattern of hybrid nanofluids. However, there are still many gaps to be filled in. This study will simulate the steady mixed convection flow in a single or double lid-driven cavity filled with hybrid nanofluid (Al2O3-Cu-water). The fluid is assumed to be Newtonian and laminar. The flow is two-dimensional and incompressible. Nanoparticles are assumed in a spherical shape. Firstly, the fluid flow pattern and heat transfer behavior on mixed convection in a lid-driven square cavity filled with hybrid nanofluid with cold sidewalls was studied. The bottom wall was uniformly heated, while the top wall was adiabatic. Mixed convection in a double lid-driven horizontal rectangular cavity filled with hybrid nanofluid was determined in the second problem. Non-uniform heating distribution on both horizontal walls was studied in the third problem. Finally, the inclined magnetic field's influences and cavity on mixed convection in a lid-driven rectangular cavity-filled hybrid nanofluid were analyzed. The dimensionless governing equations were formulated by using appropriate reference variables. These equations were solved using the finite volume method. The convection-diffusion terms were discretized using the power-law scheme, while the pressure and velocity components were coupled using the SIMPLE algorithms. The resultant matrices were then solved iteratively using the Tri-Diagonal Matrix Algorithm coded in FORTRAN90. The present solutions obtained were then compared with previous studies, and a good agreement was found. The numerical results were presented in the forms of isotherm and streamline. The results show that the flow circulation strength is enhanced by the hybrid nanofluid addition due to the hybrid nanoparticles' higher thermal conductivity compared with the nanofluids.